2005
DOI: 10.2134/jeq2004.0407
|View full text |Cite
|
Sign up to set email alerts
|

Rhizospheric Mobilization and Plant Uptake of Radiocesium from Weathered Micas

Abstract: Acute K depletion in the rhizosphere can lead to increased root uptake of radiocesium. Two processes can govern this increase: the very low uptake of potassium and the weathering of Cs-fixing clay minerals. Their respective importance is, however, unknown. We investigated the effects of these processes on radiocesium mobilization by roots of willow (Salix viminalis L.) from three micas: muscovite, biotite, and phlogopite. Willows were grown in a mixed quartz-mica substrate with the three respective (134)Cs-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Consequently, as ECM fungi can immobilize radiocesium and limit its accumulation in plants and especially shoots, they appear to be good candidates for phytoremediation strategies orientated towards the stabilization of radiocesium. It should nevertheless be noticed that along with ECM fungi, other soil-borne fungi are involved in radiocesium immobilization (Tegen et al, 1991;Brückmann and Wolters, 1994;Wirth et al, 1994;Rafferty et al, 1997) and are important agents in the radiocesium cycle in the upper layers of forest soils (Dighton et al, 1991;Thiry and Myttenaere, 1993;Guillitte et al, 1994). They indeed strongly affect radiocesium mobility and make it temporarily unavailable to the other components in the ecosystem.…”
Section: Ecm Fungimentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, as ECM fungi can immobilize radiocesium and limit its accumulation in plants and especially shoots, they appear to be good candidates for phytoremediation strategies orientated towards the stabilization of radiocesium. It should nevertheless be noticed that along with ECM fungi, other soil-borne fungi are involved in radiocesium immobilization (Tegen et al, 1991;Brückmann and Wolters, 1994;Wirth et al, 1994;Rafferty et al, 1997) and are important agents in the radiocesium cycle in the upper layers of forest soils (Dighton et al, 1991;Thiry and Myttenaere, 1993;Guillitte et al, 1994). They indeed strongly affect radiocesium mobility and make it temporarily unavailable to the other components in the ecosystem.…”
Section: Ecm Fungimentioning
confidence: 99%
“…This implies that radiocesium displays low mobility in the soil profile after its deposition due to its specific sorption on micaceous clay minerals (Cawse, 1983;Cremers et al, 1988Cremers et al, , 1990Smith and Elder, 1999;Rosén et al, 1999;Delvaux et al, 2000Delvaux et al, , 2001 and relatively high mobility in biological systems (Carter, 1993). This low mobility in soil is problematic as radiocesium tends to persist in the upper soil layers (Thiry and Myttenaere, 1993;Kruyts and Delvaux, 2002;Kruyts et al, 2004), which are extensively explored by plant roots and soil micro-organisms. Thus, in terrestrial ecosystems, the principal route of radiocesium entry into the food chain is the soil-to-plant pathway (Coughtrey and Thorne, 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was considered to be due to a slow and continued release of K from mica through the weathering process. Another reason might be due to high fixing capacity of waste mica for cesium (Zachara et al, 2002;Thiry et al, 2005;Sreenivasa Chari, 2010). The data revealed that soil type significantly influenced the 134 Cs transfer factors.…”
Section: Effect Of Waste Mica On Transfer Factors Of 134 Cs To Spinacmentioning
confidence: 99%
“…It has been also reported the K depletion in rhizosphere result in increase in plant uptake of RCs. 10,22,23) It is also noted that vermiculite which originated from the weathering of granite is one of major clay minerals produced in Fukushima, Japan.…”
Section: Introductionmentioning
confidence: 99%